PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE TRUE OR FALSE STATEMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 MUARA BUNGO TAHUN PELAJARAN 2013/2014 - Rahayu, Sri; Aima, Zulfitri; Mardiyah, Ainil (Pendidikan Matematika, 2013)
This research is from the background of the student in SMPN 5 MuaraBungo not have enough concept comprehension. That is couse the lesson still concentrate on the teacher and many of student only imitate their classmates exercise, this research have a parpose to see that is mathematics concept comprehension of the student with the active lesson application True Or False Statement type is more good than mathematics concept comprehension of the student with convensional lesson. Kind of research is experiment researchÂ  with research design is random about subjek. Population in this research is the VIII grade. Sample removal technic is random, the VIII.2 grade is choose as experiment class and VIII.4 is choose as control class. Instrument that use is the last mathematics concept comprehension test. Type of the test is essay with test realibityisÂ  r11 = 0,97. Analysis technic is t test with MINITAB. Be based on data analysis, we know that two sample class have a normal distribution an have a homogeneity with 95% trust level. The result of hypothesis test we have P-value= 0,004is that mean more low than Î± = 0,05, so the hypothesis of this research is receive than it can be interpret that mathematics concept comprehension of the student with the active lesson application True Or False Statement type is more good than mathematics concept comprehension of the student with convensional lesson in VIII grade SMPN 5 MuaraBungo lesson year 2013/2014.